From Jewish prayer to Christian ritual: early interpretations of the Lord's prayer - Clark, David A. (2014)
The fundamental premise of this work is that the meaning of a Biblical text is the history of its meaning. The interpreter must take note of the experience in which a text originated, and the settings in which it has been encountered. This essay surveys the ‘history of effects’ (Wirkungsgeschichte) of the Lord’s Prayer from the time of Jesus Christ until the beginning of the third century. In the beginning chapters, significant attention is devoted to the context of prayer in first-century Palestine and the continuity between the Lord’s Prayer and Jewish tradition. Subsequent chapters survey the presentation of the Lord’s Prayer in the Gospels of Matthew and Luke, the Didache, and Tertullian’s De oratione. Each stage of interpretation is evaluated in the light of its continuity and discontinuity with its anterior history of reception. This work concludes with an evaluation of how the notions of diachronic creativity and synchronic continuity illuminate the progressive interpretations of the Lord’s Prayer during the period under consideration.